The Influence of Organizational Culture on the Performance of Madrasah Tsanawiyah Teachers in the City of Padang - Aprizal Ahmad; Kiki Elfi Lestari (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2021)
This study aims to determine and describe the influence of organizational culture on the performance of Madrasah teachers in Padang City. An open organizational climate is a healthy climate and is highly coveted by teachers. The condition of the school organizational climate is still not good if there are still frequent conflicts between teachers and miscommunication between teachers and principals, employees with teachers, and employees with principals, so that the organizational climate of this school needs to be researched in the hope of improving the existing climate in the school. schools and can improve teacher performance better. Teacher performance is the most important input in the implementation of education. A person's performance is influenced by several direct and indirect factors. Direct factors that affect a person's performance such as individual, organizational, and psychological factors. Teacher performance as a set of teacher abilities to carry out their duties and functions as well as their responsibilities to improve student learning achievement. Based on the results of research and data analysis, it can be concluded that organizational culture significantly influences the performance of madrasa teachers. The low achievement and learning outcomes of madrasah students are caused by the low performance of madrasah teachers and is still below the minimum standard. This is because the average teacher performance in planning, implementing, and evaluating learning is still below the minimum performance standard.